Analyse de données en apprentissage d'une L2 en situation d'autonomie dans un environnement multimédia - Lise Duquette (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article suggests a methodological framework which can be used to study learning and evaluation in Computer-Assisted Language Learning (CALL) within the context of learner autonomy. Since there is at present no widely agreed upon paradigm in the field, the author suggests a methodology based on problem solving in the cognitive sciences and suggests that this methodology is generalizable to analyses of data in the context of self-directed learning in CALL. The framework for analysis consists of three general strategies related to pre-existing knowledge—regulation, application and evaluation. These strategies can be used to differentiate efficient from inefficient learners in a self-directed learning situation because they evoke learners´ previous knowledge. These general strategies are cross-categorized with six levels of problem solving: reading, analysis, exploration, planning, realization and verification. Referring to two empirical studies conducted by the author, it is shown that the suggested problem-solving framework facilitates the evaluation of learner efficiency in a self-directed learning situation in a CALL environment. Moreover, it is argued that this problem-solving framework should be used in other studies in different computer-assisted learning environments. Such research would contribute to the robustness and generalizability of the framework and thus support the wide-spread adoption of the cognitive paradigm in the area of CALL.